Karakteristik Rumah Tradisional Di Pesisir Kilen Jawa Tengah Studi Kasus Rumah Tradisional di Desa Krajan Kulon, Kaliwungu, Kendal - (Program Arsitektur, Fakultas Teknik, Universitas PGRI Semarang), Muhammad Agung Wahyudi (Teknis, 2015)
Indonesia, which consists of various ethnics are very rich in cultural products are implemented in many forms, including traditional buildings such as residential houses. Each region has a distinctive form of traditional houses, which are formed by climatic conditions, social, cultural and religious influence. Research and assessment of the traditional architecture of this house has been done, but the numbers are still inadequate because of the many types of traditional houses are scattered in various parts of Indonesia. From the treasures of traditional architecture is actually a lot that can be learned and developed in contemporary architectural design archipelago. Kaliwungu is a district town in the west of the city, in the region of Javanese culture located in the coastal area Kilen. Traditional houses in this Kaliwungu has a distinctive character that is unique and different from other traditional houses in Central Java. This study seeks to reveal the characteristics of a traditional house Kaliwungu and its comparison with traditional Javanese house in another area. An understanding of the characteristics of a traditional house Kaliwungu is useful to develop an understanding of the architecture of the archipelago, is also useful as a cultural and tourism development in Kaliwungu.Keywords: traditional house, kaliwungu, java north coastal.